Bioenergetics of a slalom kayak (K1) competition - Zamparo, P.; Tomadini, S.; Didone F.; Grazzina, F.; Rejc, E.; Capelli, C. (International Journal of Sports Medicine, 2006)
The aim of this study was: i) to compute an energy balance of a slalom kayak competition by measuring the percentage contributions of the aerobic and anaerobic energy sources to total metabolic power (Etot); and ii) to compare these data with those obtained, on the same subjects, over a flat-water course covered at maximal speed in a comparable time. Experiments were performed on eight middle- to high-class slalom kayakers (24.8 ± 8.1 years of age, 1.75 ± 0.04 m of stature, and 69.8 ± 4.7 kg of body mass) who completed the slalom race in 85.8 ± 5.3 s and covered the flat water course in 88.1 ± 7.7 s. Etot was calculated from measures of oxygen consumption and of blood lactate concentration: it was about 30 % larger during the flat water all-out test (1.72 ± 0.18 kW) than during the slalom race (1.35 ± 0.12 kW). However, in both cases, about 50 % of Etot derives from aerobic and about 50 % from anaerobic energy sources. These data suggest that, besides training for skill acquisition and for improving anaerobic power, some high intensity, cardiovascular conditioning should be inserted in the training programs of the athletes specialised in this sport.